SISTEM BUY NOW PAY LATER, SEBUAH “PERBUDAKAN” MASA KINI: MASALAH DAN SOLUSI - Muhammad Aulia Rahman; Agustina Rahayu Husein; Adied Najiyurrahman (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
The rapid development of information and communication technology has brought various conveniences, particularly in the financial technology sector through the Buy Now Pay Later (BNPL) system, which allows consumers to purchase goods without upfront payment. Based on literature review and analytical reflection, this study identifies several hidden risks of BNPL usage, including the increase of consumptive behavior that encourages individuals to continuously work in order to repay installments accompanied by additional fees and late payment penalties. Such conditions potentially lead to both material and psychological losses. Islam explicitly prohibits extravagance as stated in Qur'an Surah Al-Isra verse 27 and warns against transactions containing elements of usury (riba), which may result in social and moral harm. This study argues that BNPL may function as a form of modern economic enslavement when used excessively and without proper financial awareness. Therefore, the proposed solutions include adopting a minimalist lifestyle and cultivating the value of qana’ah (contentment) as preventive measures to reduce dependence on BNPL and to promote financial responsibility in accordance with Islamic economic principles.